2023
DOI: 10.3390/healthcare11030430
|View full text |Cite
|
Sign up to set email alerts
|

Empowering Self-Efficacy by Using Patient Empowerment among Chronic Obstructive Pulmonary Disease: Pre–Post-Test Study

Abstract: Patient empowerment is increasingly acknowledged as a milestone of high-quality patient-centered care. This study was conducted using COPD Self-Efficacy Scale to determine the effectiveness of the patient empowerment intervention program among chronic obstructive pulmonary disease patients on self-efficacy. We employed an interventional design with a pre-test and post-test. Sixty COPD patients comprised the final sample of the study. The current study revealed significant improvement in overall self-efficacy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Their study found a significant direct correlation between the patients' self-efficacy and cardiovascular risk factors, and the correlation between reduced salt intake and reduced stress was more significant; while self-efficacy and physical performance were also significantly correlated (16). In the study by Ahmed et al in Egypt, the effect of empowerment programs on improving self-efficacy in COPD patients was approved (26). In patients with chronic heart disease and COPD, as in the other chronic diseases mentioned earlier, the effect of self-care and empowerment has been positive.…”
Section: Discussionmentioning
confidence: 98%
“…Their study found a significant direct correlation between the patients' self-efficacy and cardiovascular risk factors, and the correlation between reduced salt intake and reduced stress was more significant; while self-efficacy and physical performance were also significantly correlated (16). In the study by Ahmed et al in Egypt, the effect of empowerment programs on improving self-efficacy in COPD patients was approved (26). In patients with chronic heart disease and COPD, as in the other chronic diseases mentioned earlier, the effect of self-care and empowerment has been positive.…”
Section: Discussionmentioning
confidence: 98%
“… 37 39 This improvement could be attributed to increased exposure to health information and familiarity with electronic health resources. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Healthy lifestyle behaviors are considered important means to reduce the burden of diseases as well as bring the person's general health to the highest level of well-being and self-efficacy. 1 3 University life is a critical period among students since they take on new responsibilities and decision-making roles when they arise away from their homes and families. 4 Many studies proved that healthy lifestyle behaviors had a significant impact on undergraduate student's life, and they are prone to share risky behaviors resulting in a significant impairment in health status.…”
Section: Introductionmentioning
confidence: 99%
“…Severity of COPD was divided into group A, B, C, and D according to the number of exacerbations per year, number of exacerbations requiring hospitalization per year, dyspnea according to the modified medical research council dyspnea score (mMRC) [ 19 ]. Data regarding knowledge about pulmonary rehabilitation was also collected.…”
Section: Methodsmentioning
confidence: 99%